A universidade corporativa e a universidade de educação superior - Ferronatto, Sibeli Paulon (2005)
This work has as great purpose to research Corporative University in Brazilian company, and go for verify if the denomination of University employed to inside structure of corporative education is associated to origin of Brazilian University of Superior Education (UES). As question of research has: the conception and the actions of Corporative University, in Brazilian company, they are associated a generation and dissemination of knowledge as University of Superior Education? To answer it go for realize the following purposes: to describe the principles that characterize the UEs in Brazil, they identified their conception and their actions: to review the Brazilian literature, conception, examples and reports about the UCs developed a contextualization of theme in Brazil and characterized them; identify the conception and the actions of the UCs ; to analyze relation between UC and UES, in that refer to conception and the actions; and to verify till where the Corporative University has its conception and actions associated to generation and dissemination of knowledge as objectify as UEs . The theoretical referential researched in the search. This was divided in three subtitle: the evolution of administration knowledge in the organization (practice of personnel, development of human wealth and corporative education); University Superior Education (conception and actions); and Corporative University (conception). Then they were formulated eight principles that they characterize UES , that they are philosophic, liberty, basic and general formation, instruction, research, extension, of democracy and cultural practice. The applicable methodology in the study was a research with approach empírico-analítica , of type survey, with application of a questionary to twelve company that they possess their structure of education called Corporative Education and the they are among the best (a hundred) companies to work in Brazil and among the best and great companies in Brazil, both in edition of Magazine Exame , April publishing. The variables of research are conception and action of University and they were operationally though Likert method (Administrative System, in a continued one to twenty). For analyze used of electronic designs and calculations of formulas as means and count, in which they generated graphs and helped in the conclusion of research. As the conclusion of work has that Corporative University possessed the philosophic principles, of liberty, of basic and general formation, of instruction, of research, of extension, of democracy and cultural practice and it don t possess the principle of democracy. Thus, denomination of UNIVERSITY is according with the conception and the actions of UESs . As the suggestion for new researches detach the necessity of verify for that matter the actions of the instruction, developed research and extension for UCs is been developed and make good use at the organization, as well as if they are generating knowledge and the desired results for the companies, used as methodology a quantity research.